2021
DOI: 10.1038/s41598-021-84211-y
|View full text |Cite
|
Sign up to set email alerts
|

Identifying gene expression patterns associated with drug-specific survival in cancer patients

Abstract: The ability to predict the efficacy of cancer treatments is a longstanding goal of precision medicine that requires improved understanding of molecular interactions with drugs and the discovery of biomarkers of drug response. Identifying genes whose expression influences drug sensitivity can help address both of these needs, elucidating the molecular pathways involved in drug efficacy and providing potential ways to predict new patients’ response to available therapies. In this study, we integrated cancer type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…In each of these 59 miRNA-mediated gene-cancer-drug combinations, since both the miRNA and the target gene were predictive of survival difference in the corresponding cancer-drug group, these combinations may reflect the functional role of the miRNA markers in affecting drug response through modulating the expression of their target genes. Interestingly, we observed miR-18a and its target gene SMAD4 were predictive of carboplatin response in HNSC, which was consistent with our previous study on the relationship between SMAD4 and carboplatin response 38 . Additionally, we also identified miR-18a to be predictive of the prognosis of HNSC patients treated with cetuximab.…”
Section: Resultssupporting
confidence: 92%
“…In each of these 59 miRNA-mediated gene-cancer-drug combinations, since both the miRNA and the target gene were predictive of survival difference in the corresponding cancer-drug group, these combinations may reflect the functional role of the miRNA markers in affecting drug response through modulating the expression of their target genes. Interestingly, we observed miR-18a and its target gene SMAD4 were predictive of carboplatin response in HNSC, which was consistent with our previous study on the relationship between SMAD4 and carboplatin response 38 . Additionally, we also identified miR-18a to be predictive of the prognosis of HNSC patients treated with cetuximab.…”
Section: Resultssupporting
confidence: 92%
“…One of the most significantly differentially regulated genes between HPV+ versus HPV- PDX tumors was C19orf57 ( BRME1 ), which demonstrated 6-fold higher expression in HPV+ models compared to HPV- models (p = 7x10 -17 ; Table 2 ). A previous study of TCGA patients with a variety of tumor types identified an association between high C19orf57 expression with superior survival on cisplatin therapy compared to low C19orf57 expression in cervical squamous cell carcinoma and endocervical adenocarcinoma [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…This protein plays a key role in meiotic recombination by facilitating homology-directed DNA repair via recruitment of recombinases such as RAD51 to DNA double-strand breaks in gametes [ 32 ]. A study that analyzed the correlation between tumor gene expression and patient survival on chemotherapy found that the top gene-drug interaction among patients with cervical squamous cell carcinoma and endocervical adenocarcinoma was that of C19orf57 and cisplatin [ 16 ]. Specifically, high C19orf57 expression was associated with improved survival in the setting of cisplatin therapy relative to the survival of patients whose tumors expressed lower levels of C19orf57 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is especially suited for identifying biomarkers predictive of drug response because the molecular assays are performed on pre-treatment samples, representing the state of a tumor at the point when treatment decisions are made. Our group has previously identified molecular features associated with drug-specific survival using the TCGA gene expression, 29 copy number variation, 30,31 protein, 32 and miRNA 33 datasets. While the high dimensionality of the methylation dataset makes it the most challenging to analyze, the promise that DNA methylation holds as a source of biomarkers as well as our success with these other molecular data types make it a critical dataset to explore for molecular features related to drug efficacy.…”
Section: Introductionmentioning
confidence: 99%